2014
DOI: 10.1016/j.jbtep.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Rumination prospectively predicts executive functioning impairments in adolescents

Abstract: Background and objectives The current study tested the resource allocation hypothesis, examining whether baseline rumination or depressive symptom levels prospectively predicted deficits in executive functioning in an adolescent sample. The alternative to this hypothesis was also evaluated by testing whether lower initial levels of executive functioning predicted increases in rumination or depressive symptoms at follow-up. Methods A community sample of 200 adolescents (ages 12–13) completed measures of depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 66 publications
(119 reference statements)
4
62
1
Order By: Relevance
“…The seeming lack of evidence for neuropsychological deficits in depressive disorders in children and adolescents is echoed in community studies that have looked at the relationship of EF and depressive symptoms in nonclinical samples [17,61]. In the largest community study with more than 1,800 participants that were followed over 5 years a few noteworthy findings emerged [76]: first, this study found significant gender differences in neurocognitive performance in accord with previous findings in developmental studies of typically developing children (e.g.…”
Section: Discussionsupporting
confidence: 69%
“…The seeming lack of evidence for neuropsychological deficits in depressive disorders in children and adolescents is echoed in community studies that have looked at the relationship of EF and depressive symptoms in nonclinical samples [17,61]. In the largest community study with more than 1,800 participants that were followed over 5 years a few noteworthy findings emerged [76]: first, this study found significant gender differences in neurocognitive performance in accord with previous findings in developmental studies of typically developing children (e.g.…”
Section: Discussionsupporting
confidence: 69%
“…The present study examined the relationship of rumination and depression to deficits in executive functions in early adolescence, a critical developmental period for the emergence of depression and rumination and the development of executive functions. Evidence exists linking deficits on emotionally neutral tests of executive functions with rumination in adults (e.g., Altamirano et al, 2010; Whitmer & Banich, 2007), but only a few studies have examined whether children or adolescents who ruminate exhibit similar patterns of impairment, and these have yielded inconsistent findings (Connolly et al, 2014; Wilkinson & Goodyer, 2006). Although adults with diagnoses of unipolar depression have been found to exhibit executive functions deficits during the acute phase of the disorder, evidence in younger samples is inconsistent (e.g., Baune et al, 2012; Cataldo et al, 2005; Frost et al, 1989; Gunther et al, 2011, 2004; Kyte et al, 2005; Maalouf et al, 2011; Micco et al, 2009; Wilkinson & Goodyer, 2006), and it is unclear whether observed deficits are state dependent, normalizing when depression remits, or are trait markers of the disorder that persist beyond remission (Hasselbalch, Knorr, & Kessing, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a new conceptual model details the limitations in attentional processing that accompany chronic rumination (see Whitmer & Gotlib, 2013), and some data indicate that rumination is linked with reductions in elements of executive functioning (e.g., Connolly et al, 2014). This link with attentional problems has troubling implications for perfectionists at school or work who characteristically brood, but must learn and remember new material.…”
Section: Diminished Attention and Cognitive Capacitymentioning
confidence: 99%